Sustainability reports of Chilean, Spanish and Mexican companies: a critical genre analysis - Basanta, Almudena; Vangehuchten, Lieve (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This article presents a critical genre analysis of the sustainability report in three of the main dialectological variants of the Spanish language, namely Chilean, Mexican and peninsular Spanish, which also correspond to three areas with different levels of Corporate Social Responsibility (CSR) implementation. The corpus consists of the reports of six companies in the extractive and financial sectors, which are particularly sensitive to sustainability and face great challenges in achieving a balance between people, planet and profit. We assume that CSR discourse is a hybrid form of business communication which, in addition to its primary informational role, performs the communication functions of legitimising the company's actions, managing its reputation and establishing a sustainable dialogue with stakeholders. Through a lexical-semantic discursive analysis that makes use of topic modelling, the reports of the three sub-corpuses are compared and it is concluded that in the peninsular sub-corpus CSR communication is mainly of a strategic nature, while in the Chilean and Mexican sub-corpus it is also clearly responsive, which can be explained from a transcultural and institutional perspective. As for the interdiscourses that serve to reinforce the general CSR discourse, it is striking that the Chilean and Mexican reports make significantly more use of the communication strategies of legitimacy and reputation, so that they clearly want to exploit the report's promotional potential more than seems to be the case in the peninsular subcorpus. Finally, when taking into account the extra-textual factors, it can be seen that the strategy of omission also has an important influence on the discourse of this genre.